2012
DOI: 10.4236/ojanes.2012.24043
|View full text |Cite
|
Sign up to set email alerts
|

Pseudocholinesterase Deficiency: A Case Report and Literature Review

Abstract: A 72-year-old male underwent neck dissection and parotidectomy with facial nerve preservation. Endotracheal intubation was facilitated with succinylcholine. Prolonged muscle paralysis which was first detected after failure to stimulate the facial nerve with electrocautery, lasted five hours. Laboratory tests indicated pseudocholinesterase (PChE) deficiency. A thyroidectomy one month later was performed uneventfully using rocuronium as a muscle relaxant. Literature review revealed a total of 40 PChE deficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 32 publications
(59 reference statements)
0
13
0
Order By: Relevance
“…In inherited PChE deficiency, succinylcholine and mivacurium cannot be hydrolyzed by atypical PChE. The majority of people (96%) are homozygous for the normal PChE genotype and the remaining individuals (4%) carry 1 or much more of the atypical gene alleles [11]. A small minority of the people (0.2%, 1 per 480) carry both enzymes (heterozygous), and these patients hydrolyze succinylcholine in a longer time.…”
Section: Discussionmentioning
confidence: 99%
“…In inherited PChE deficiency, succinylcholine and mivacurium cannot be hydrolyzed by atypical PChE. The majority of people (96%) are homozygous for the normal PChE genotype and the remaining individuals (4%) carry 1 or much more of the atypical gene alleles [11]. A small minority of the people (0.2%, 1 per 480) carry both enzymes (heterozygous), and these patients hydrolyze succinylcholine in a longer time.…”
Section: Discussionmentioning
confidence: 99%
“…Hackett et al found that the length of paralysis ranges from 50 minutes to ten hours 4 . The first documented case report was in 1956 4 . In 1978 Viby-Mogensen et al reviewed 225 cases of prolonged apnea following suxamethonium 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The immediate management of suxamethonium apnea is to continue appropriate sedation and mechanical ventilation and wait for a spontaneous recovery in the ICU setting 1,12. The use of pharmacological reversal agents, such as anticholinesterases and neostigmine, are avoided as they could lead to worsening of the condition 1,4 .…”
Section: Discussionmentioning
confidence: 99%
“…Pseudocholinesterase (PChE) is a plasma protein synthesized by the liver that has an enzymatic activity of ester hydrolysis, which is important in the metabolism of a number of commonly used medications. 10–12 Biologically active esters requiring PChE for metabolism include the depolarizing neuromuscular blocking agent succinylcholine and the nondepolarizing neuromuscular blocking agent mivacurium. PChE deficiency is a rare but potentially critical cause of postoperative morbidity, manifesting as unexpected, prolonged paralysis, apnea, and delayed emergence following general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of PChE deficiency is estimated to be 1:3,000 to 1:10,000 for homozygotes and up to 1:25 for heterozygotes. 10 Acquired causes of PChE deficiency include chronic liver disease, malnutrition, pregnancy, and malignancy and are hypothesized to be due to reduced levels of circulating enzyme. 11 Cholinesterase inhibitors, pancuronium, oral contraceptives, metoclopramide, esmolol, phenelzine, echothiophate eye drops, organophosphate insecticides, and cyclophosphamide are drugs that have been shown to attenuate PChE activity.…”
Section: Introductionmentioning
confidence: 99%